2019
DOI: 10.1080/1828051x.2018.1548914
|View full text |Cite
|
Sign up to set email alerts
|

Impact of theSpirulina maximaextract addition to semen extender on bovine sperm quality

Abstract: The present study was undertaken to investigate an effect of various concentrations of Spirulina maxima extract (SME) in BIOXcell V R extender on Simmental bulls spermatozoa quality. Semen was collected from 20 healthy bulls using an artificial vagina. Semen was evaluated in terms of concentration, motility, viability and morphology. Samples that showed more than 70% motility, 60% viability and 70% morphologically accepted spermatozoa were selected for the experiment. SME at the concentrations of 2, 4, 6 and 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 37 publications
(28 reference statements)
4
20
1
7
Order By: Relevance
“…Semen was automatically packed (Bloc Machine FIN, IS 4, France) into polyvinyl chloride (PVC) straws (0.25 mL) (Biovet, France) which were filled and equilibrated for 1.5 h at 4 °C. After equilibration, the straws were frozen in liquid nitrogen vapor using a computer controlled automatic freezer from 4 to − 15 °C at the rate of − 3 °C /min and from − 15 to − 80 °C at the rate of − 10 °C /min (IMV Technologies, France) 23 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Semen was automatically packed (Bloc Machine FIN, IS 4, France) into polyvinyl chloride (PVC) straws (0.25 mL) (Biovet, France) which were filled and equilibrated for 1.5 h at 4 °C. After equilibration, the straws were frozen in liquid nitrogen vapor using a computer controlled automatic freezer from 4 to − 15 °C at the rate of − 3 °C /min and from − 15 to − 80 °C at the rate of − 10 °C /min (IMV Technologies, France) 23 .…”
Section: Methodsmentioning
confidence: 99%
“…Mass motility was examined in 20 µL of semen which was placed on a prewarmed slide without any cover slip and analyzed under microscope (Nikon E 200, China) equipped with phase-contrast optics (100×) 24 . The mass motility was scored into four scales: + no motion, ++ free spermatozoa moving without forming any waves, +++ vigorous movement with moderately rapid waves, ++++ very rapidly moving waves 23 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Khan et al (89) found that adding green tea extract at an inclusion level of 0.75% protected the plasma membrane and increased motility rates of cryopreserved spermatozoon. The addition of Spirulina maxima Extract (SME), a microalga, to extender has exhibited positive effects on post-thaw semen parameters including sperm motility and morphology, and marked reduction in ROS synthesis (90). Other natural compounds have been found to act as an antioxidant.…”
Section: Extender Developmentmentioning
confidence: 99%
“…Increasing lipid peroxidation results in reducing motility (Opuwari and Henkel, 2016), fragmentation of DNA and reducing sperm fertilizing ability (Attia et al, 2019). Also, an excessive ROS production exceed the antioxidant capacity of the seminal plasma, leading to damaged mitochondria and membranes (acrosomal and plasma) of spermatozoa (Mizeraa et al, 2019). New alternative approaches to improve buck fertility kept under unfavorable reproductive seasons are demanded (Okab et al, 2013).…”
Section: Introductionmentioning
confidence: 99%